Aplicativo móvel para rastreamento - estudo de caso : monitoramento de ônibus circular da UFPA. - REIS, Diórgino Rigles Alves (2020)
The feature of geolocation, introduced in smartphones, is present in a series of applications to identify the location of points of interest or to define efficient routes of movement. Therefore, this paper presents the development of a tracking mobile app, aiming to propose a simple and accessible solution for the tracking of devices attached to goods or people. The application is divided in two modules: Tracking, used to get the location coordinates of the tracked device, and User, used to track the movement of a particular device throughout the map. The application was developed in Android, using Google Maps API, GPS, and webservice technology, which is responsible for intermediating the communication between the modules and the MySQL database. A case study was conducted within the Federal University of Pará, by the use of the application in the monitoring of the Circular bus. Thus, it was possible to verify the actual operation of the application as well as the benefits that this could bring to the academic community.